2016
DOI: 10.1111/1744-9987.12400
|View full text |Cite
|
Sign up to set email alerts
|

Daily Home Hemodialysis Is an Available Option for Renal Replacement Therapy in Spain

Abstract: The objective of the present study was to analyze the characteristics and survival of patients from our hospital who started home hemodialysis. We analyzed all patients receiving home hemodialysis from 1969 to 2015 (51 patients; age 45 ± 23 years; men 77%). We collected characteristics, hospital admission, and mortality. After a median follow-up of 43 (22-76) months, we found 0-1 hospital admissions per year. Sixty-nine percent received a kidney transplant, and the global mortality was 10%. Survival at 5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Xu et al found no obvious changes of BUN [15] and Epo in either groups after sodium ferrous chlorophyll treatment of hemodialysis patients; whereas, Epo dosage was decreased more significantly than in the control group (P < 0.05). Vega et al found the mean equivalent renal urea clearance at [16] 15.6 ± 4.2 mL/min and the Epo resistance index at 3.7 ± 2.1 IU/kg/week/g/dL in patients who received home hemodialysis. Ibrahim et al [17] exhibited reduced serum levels of Epo and increases in the kidney function markers (urea and creatinine) in male Wistar rats of induced diabetes mellitus than control ones.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al found no obvious changes of BUN [15] and Epo in either groups after sodium ferrous chlorophyll treatment of hemodialysis patients; whereas, Epo dosage was decreased more significantly than in the control group (P < 0.05). Vega et al found the mean equivalent renal urea clearance at [16] 15.6 ± 4.2 mL/min and the Epo resistance index at 3.7 ± 2.1 IU/kg/week/g/dL in patients who received home hemodialysis. Ibrahim et al [17] exhibited reduced serum levels of Epo and increases in the kidney function markers (urea and creatinine) in male Wistar rats of induced diabetes mellitus than control ones.…”
Section: Discussionmentioning
confidence: 99%
“…Para ello, es fundamental que los propios profesionales sanitarios implicados en la comunicación/divulgación de la HDD crean en ella. La supervivencia de los pacientes que se dializan en HDD intensiva o diaria, es otro de los factores dignos de resaltar 45 . Frente a otras modalidades como son la HD en el centro o la diálisis peritoneal, la HDD diaria o intensiva presenta mejores resultados, si bien las series publicadas son pequeñas respecto a las de las otras modalidades.…”
Section: Discussionunclassified
“…The failure of early dialysis to prolong life and improve its quality has caused nephrologists to reflect on the negative effects of treatment [7,115,116,117,118,119,120]. This was also the starting point for reconsidering incremental dialysis and for realizing that, especially in elderly patients, the advantages of a high dialysis dose are often counterbalanced by the iatrogenicity of treatment [120,121,122,123,124,125]. Increasing the dialysis dose by increasing the number (and/or duration) of sessions may, conversely, be necessary in particular situations, such as pregnancy or high metabolic needs, or be a suitable way to attain tolerance in fragile individuals [49,50,51,52,53,125,126,127].…”
Section: One-size-fits-all or Tailor-made Treatments?mentioning
confidence: 99%